FMR1 and AKT/mTOR signalling pathways: potential functional interactions controlling folliculogenesis in human granulosa cells - Rehnitz, Julia; Alcoba, Diego Duarte; Hinderhofer, Katrin; Youness, Berthe; Strowitzki, Thomas; Vogt, Peter H. (Reproductive biomedicine online, 2017)
Granulosa cells (GCs) play a major role in folliculogenesis and are crucial for oocyte maturation and growth. In these cells, the mTOR/AKT signalling pathway regulates early folliculogenesis by maintaining the dormancy of primordial follicles, while FSH induces their further differentiation and maturation. Because changes in number of CGG triplets in FMR1 exon 1 (below or beyond normal values of 26-34 triplets) affect ovarian reserve and pre-mutations containing >54 CGG triplets represent a known risk factor for premature ovarian insufficiency/failure, we investigated in the human GC model (COV434) how FMR1/FMRP and mTOR/AKT are expressed and potentially interact during GC proliferation. As FMR protein (FMRP) is expressed mainly in human ovarian GCs, we used these after inducing their proliferation using recombinant FSH (rFSH) and the repression of the mTOR/AKT signalling pathway. We showed that AKT and mTOR expression levels significantly increase after stimulation with rFSH, while S6K and FMR1 expression decrease. After inhibiting mTOR and AKT, FMR1 and S6K expression significantly increased. Only AKT inhibition led to decreased FMRP levels, as expected due to the known FMR1/FMRP negative feedback loop. But rFSH and the mTOR inhibition increased them, indicating a decoupling of this FMR1/FMRP negative feedback loop in our model system.
Gesehen am 02.05.2018
Im Titel ist "FMR1" kursiv geschrieben